QIBLA DIRECTION AND CONREGATIONAL PRAYER AT THE MOSQUE WHEN MUSLIMS ARE MINORITY - Ahmad Luthfi Choirullah; Muhammad Shibghatullah (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
Prayer is an obligation for those who believe. There are several conditions for the prayer to be valid and accepted, including facing the Qibla. When Muslims become a minority in a certain area, congregational prayers are something that must be considered, including determining the direction of Qibla. Qualitative is the method used in this study. Evidence from the Al-Quran and Hadith, books and supporting articles sourced from discussions, research, supporting articles are used as references and main studies. Opinions and results of ijtihad scholars are also included to strengthen the study. Sholat merupakan kewajiban bagi orang-orang yang beriman. Ada beberapa syarat agar shalat yang dikerjakan sah dan diterima, diantaranya adalah menghadap kiblat. Ketika Umat Islam menjadi minoritas di daerah tertentu, maka sholat berjamaah menjadi sesuatu yang harus dipertimbangkan, termasuk di dalamnya menetukan arah kiblat. Kualitatif menjadi metode yang digunakan dalam studi ini. Dalil dari Al-Quran dan Hadits, Buku dan artikel-artikel pendukung yang bersumber dari diskusi, penelitian, artikel pendukung dijadikan referensi dan kajian utama. Pendapat dan hasil ijtihad ulama juga disertakan untuk memperkuat kajian.